2020
DOI: 10.1177/2515841420979111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, optical coherence tomography findings and treatment outcomes of post-fever retinitis

Abstract: Objectives: To study the clinical features, optical coherence tomography (OCT) findings, treatment options and follow-up outcomes of post-fever retinitis (PFR). Subjects: A total of 19 eyes of 13 patients, diagnosed with PFR (retinitis following febrile episode) over 2 years were retrospectively studied. Methods: Documented history, baseline clinical features and systemic investigations performed for PFR were reviewed. Fundus findings, foveal architecture on swept-source OCT, the treatment options and the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Recently Sundar et al have reported a series of post-fever retinitis cases encouraging the use of anti-VEGF and oral steroids few days after oral doxycycline. 22 In contrast to their study, group A and B in our series (total 29 eyes of 23 patients) have effectively documented good visual outcome without the need of oral steroids or anti-VEGF as reported previously. 17 Even after considering the cases where retinitis lesions were within 1 disc diameter of center of fovea, visual outcome remained good, but the number of cases were small to derive a firm conclusion.…”
Section: Discussioncontrasting
confidence: 59%
“…Recently Sundar et al have reported a series of post-fever retinitis cases encouraging the use of anti-VEGF and oral steroids few days after oral doxycycline. 22 In contrast to their study, group A and B in our series (total 29 eyes of 23 patients) have effectively documented good visual outcome without the need of oral steroids or anti-VEGF as reported previously. 17 Even after considering the cases where retinitis lesions were within 1 disc diameter of center of fovea, visual outcome remained good, but the number of cases were small to derive a firm conclusion.…”
Section: Discussioncontrasting
confidence: 59%
“…Sunder et al . [ 2 ] found better results with anti-VEGFs in their study where their patients received anti-VEGFs along with doxycycline and steroids. But a comparative study, although with a small sample size did not find an additional benefit of anti-VEGFs in ER when treated with doxycycline and steroids or even with anti-VEGF monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemic retinitis (ER) or post-fever retinitis comprises a uveitic entity with a similar morphological pattern and course of the disease but different etiologies such as rickettsia, typhoid, dengue, chikungunya, and West Nile virus. [ 1 2 ] As a rule, there is a recent history of fever with or without joint pain and skin rash. In most cases, the diagnosis of the fever remains uncertain due to non-specific systemic manifestations or lack of gold-standard investigations.…”
mentioning
confidence: 99%
“…We find this outcome comparable or even better than the previous reports. [1][2][3][4] We are of opinion that most of the cases of epidemic retinitis can be treated with oral doxycycline and without any steroids or anti-VEGF agents. Topical steroids or topical non-steroidal anti-inflammatory drugs can be added depending on anterior segment inflammation.…”
Section: Dear Editormentioning
confidence: 99%
“…We read the article ‘Clinical features, optical coherence tomography findings and treatment outcomes of post-fever retinitis’ published by Sunder and colleagues 1 with great interest. Authors have recommended the use of anti-vascular endothelial growth factor (anti-VEGF) as they found good outcome in their patients.…”
mentioning
confidence: 99%